Designing And Evaluating Training Models for Human Resource Competencies in The Digital Era - Fajar Baskoro; Muhammad Bayu Pancakusuma; Susilo Toto Raharjo (LifeSciFi, 2023)
This research investigates the evolving human resource needs at Bank Rakyat Indonesia (BRI) in response to digitalization challenges and opportunities. The study aims to identify the key competencies required for BRI's workforce to thrive in the digital transformation, emphasizing digital skills, fintech knowledge, data analytics, cybersecurity, and innovation. Additionally, the research seeks to design an optimal education and training model tailored to BRI’s needs and evaluate its effectiveness in enhancing workforce competencies. A descriptive and qualitative literature review approach was employed to examine factors influencing training effectiveness, such as technology-driven learning methods, adaptive strategies, and continuous evaluation processes. The findings suggest that BRI should adopt dynamic, technology-enhanced training approaches, including blended learning and gamification, while considering the diverse backgrounds of its workforce. Personalized training programs and strategic partnerships with educational institutions can further enrich the content and relevance of training initiatives. The study concludes that prioritizing human resource development through innovative and sustainable training models is essential for BRI to build a skilled, innovative, and adaptable workforce capable of navigating ongoing industry changes and digital challenges.